Dampak Kriminalitas Terhadap Kualitas Hidup Masyarakat Urban - Stiawan, Bayu; Yusuf, Hudi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Crime is a social phenomenon that often occurs in urban areas and has a significant impact on people's quality of life. The existence of crime, both minor and serious crimes, creates uncertainty that damages the sense of security and stability of people's daily lives. This study aims to analyze in depth how crime rates can affect various aspects of urban community life, including psychological, social, economic, and physical dimensions. To achieve this goal, this study uses a mixed methods approach, namely a combination of qualitative and quantitative methods. Data were obtained through surveys, in-depth interviews, and observations of several urban areas in Indonesia, which represent various levels of crime and socio-economic characteristics. The results of the study show that the existence of crime, both in the form of minor and serious crimes, has a negative impact on people's sense of security. This not only affects physical and social life, but also reduces the overall quality of life. In addition, crime also has an impact on decreasing social trust between residents, reducing social interaction, and worsening the quality of relationships between individuals in the community. Furthermore, the impact of crime is clearly visible in the economic aspect, where insecurity hinders economic mobility and reduces participation in social activities. The existence of crime is also closely related to mental health problems, because a constant sense of threat can cause stress, anxiety, and other psychological disorders. This study suggests that the government and policy makers strengthen efforts to combat crime through more effective and integra